The venom of the scorpion Centruroides limpidus, which causes the highest number of stings in Mexico, is neutralized by two recombinant antibody fragments. (September 2021) - Fernández-Taboada, Guillermo; Riaño-Umbarila, Lidia; Olvera-Rodríguez, Alejandro; Gómez-Ramírez, Ilse Viridiana; Losoya-Uribe, Luis Fernando; Becerril, Baltazar
Highlights: Monoclonal antibody mAb B7, specifically recognized Cl13 toxin from Centruroides limpidus venom. mAb B7 was used to obtain its respective single chain antibody fragment (scFv B7). Affinity maturation of scFv B7 was achieved by means of 3 cycles of directed evolution and phage display. The whole venom of Centruroides limpidus was neutralized by scFvs 11F and 10FG2. Abstract: Phage display and directed evolution have made it possible to generate recombinant antibodies in the format of single chain variable fragments (scFvs) capable of neutralizing different toxins and venoms of Mexican scorpions. Despite having managed to neutralize a significant number of venoms, some others have not yet been completely neutralized, due to the diversity of the toxic components present in them. An example is the venom of the scorpion Centruroides limpidus, which contains three toxins of medical importance, called Cll1, Cll2 and Cl13. The first two are neutralized by scFv 10FG2, while Cl13, due to its sequence divergence, was not even recognized. For this reason, the aim of the present work was the generation of a new scFv capable of neutralizing Cl13 toxin and thereby helping to neutralize the whole venom of this scorpion. By hybridoma technology, a monoclonal antibody (mAb B7) was generated, which was able to recognize and partially neutralize Cl13 toxin. From mAb B7, its scFv format was obtained, named scFv B7 and subjected to three cycles of directed evolution. At the end of these processes, scFv 11F which neutralized Cl13 toxin was obtained. This scFv, administered in conjunction with scFv 10FG2, allowed to fully neutralize the whole venom of Centruroides limpidus scorpion.